Characterization of encapsulated ginger essential oils and its antimicrobial properties / Tengku Shafazila Tengku Saharuddin... [et al.] - Tengku Saharuddin, Tengku Shafazila; Ozair, Lailatun Nazirah; Zulkifli, Ayuni Shahira; Hairul Shah, Nursarah Syazwani; Sahidan, Nur Syafiqah (Universiti Teknologi MARA, Negeri Sembilan, 2020)
Ginger essential oils (GEO) are natural products with antibacteria properties consisting of many different volatile compounds have high potential to be used in many applications. In this study, the ginger GEO was successfully encapsulated in chitosan as a carrier agent using a spray drying technique. The extraction of Zingiber officinale (ginger) essential oil is performed by steam distillation method. The GEO was encapsulated in chitosan as a carrier agents at 1:3, GEO:chitosan ratio by using spray drying technique. GEO together with encapsulated GEO were further assayed for antimicrobial activity by disc-diffusion method. For characterization of encapsulated GEO, Fourier transform infrared spectroscopy (FTIR) and Field emission scanning electron microscopy (FESEM) were used. FTIR analysis revealed that there was no existence of a new functional group in the encapsulated GEO showing that there is only physical interaction between GEO and chitosan. Besides, FESEM analysis showed the encapsulated GEO were in micro in sizes and possessed spherical shape with smooth and porous surface. Furthermore, Both GEO and encapsulated GEO showed in vitro antimicrobial activity against Escheriachia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Salmonella typhi with encapsulated GEO possessed higher in the activities for all studied bacteria compared to GEO. The encapsulated GEO demonstrated a superior performance against Salmonella typhi with the inhibition zone of 22.5 mm compared to GEO only 13.5 mm. The results obtained indicated that due to the volatility and instability of the GEO when exposed to environmental factors, its encapsulation considerably improve and enhanced its performance.